Kondisi Ekologis Padang Lamun Berdasarkan Jenis, Kerapatan dan Penutupan di Pantai Pengastin, Bali - Manurung, Patardo Zerubabel Williford (The NIKe Journal, 2025)
Pengastian Beach is one of the beaches with high tourism activity and ongoing development that may potentially disrupt the condition of seagrass vegetation. This study aims to assess the ecological condition of seagrass beds at Pengastian Beach by evaluating species diversity, density, and percentage cover. The research was conducted using a 50 x 50 cm quadrat transect method at 33 sampling points across 3 stations, with each station containing 11 points. Three seagrass species were identified: Syringodium isoetifolium, Cymodocea rotundata, and Thalassia hemprichii. Seagrass density ranged from 321 to 900 individuals per square meter (ind/m²). The percentage of seagrass cover ranged from 0 to 15%, indicating that the seagrass beds are in a very poor condition. The average temperature at Pengastian Beach ranged from 28.4°C to 28.8°C. The beach has a low salinity level of 20 ppt. The current velocity ranged from 1.2 to 1.5 meters per second. Water clarity was recorded at 95%, and the water depth was measured at 92 cm. The pH levels ranged from 8.08 to 8.12. The results show that the seagrass species Thalassia hemprichii had a very low density, while Syringodium isoetifolium had the highest density among the observed species. Ecologically, Pengastian Beach is experiencing environmental stress and requires sustainable management.